208 Arterial Inflammation and Calcification in Patients with Lower Limb Atherosclerosis using PET/CT Analysis: A Proof-of-Principle Study. (6th June 2015) - Chowdhury, Mohammed; Tarkin, Jason; Makris, Grigoris; Rudd, James; Coughlin, Patrick
Abstract : Introduction: Lower limb peripheral arterial disease (PAD) is common. Atherosclerotic development is linked with inflammatory and calcific processes occurring at the vessel wall, having been evaluated in the coronary and carotid circulation using PET/CT analysis with the 18F FDG (inflammation) and 18F NaF (calcification) tracers. Methods: 8 patients (16 legs; 5 men, median age 74.5 years; IQR (69.5–77.5)) with a diagnosis of intermittent claudication were prospectively recruited to the study. PET/CT analysis was undertaken in each patient using both tracers. The lower limb arterial tree was examined from the aortic bifurcation to the ankle. The degree of arterial calcification (AC) was measured using a modified Agatston score. Arterial 18F-NaF and 18F-FDG uptake was determined using standard protocols and measured by drawing regions of interest and normalised to tracer levels in the common femoral vein to obtain the arterial target-to-background ratio (TBR). Correlation between tracer uptake and AC was determined using Pearson's correlation. Results: The overall whole limb median (IQR) TBR levels for 18F NaF was 1.30 (0.98–1.74) and for 18F FDG was 1.42 (1.11–1.75). The median limb AC score was 1954.5 (1198–3216). A positive correlation was observed when arterial 18F FDG uptake was correlated with 18F NaF uptake (p = 0.000, r = 0.611) and AC score (p = 0.009, r = 0.654). An inverse correlation was found when correlating 18F NaF tracer uptake with AC score (p = 0.004, r=–0.765). Conclusion: Lower limb disease progression will lead to increased atherosclerotic burden with a potential risk of amputation. This study is the first to determine the inter-relationship between inflammation and calcification within the lower limb arterial tree. Further studies are required to look at longer-term sequelae of atherosclerotic progression/development.